Communicating the UX vision 13 anti-patterns that block good ideas - Hodges-Schell, Martina; O'Brien, James (Amsterdam Boston Morgan Kaufmann, 2015)
This book identifies the 13 main challenges designers face when they talk about their work and provides communication strategies so that a better design, not a louder argument, is what makes it into the world. Communicating the UX vision helps you identify the skills and behavioral patterns to present your work in more persuasive ways, and respond more constructively to feedback from coworkers and stakeholders
Speaking different languages -- Having different KPIs -- Not embracing everyone's goals -- Presenting without contextualizing -- Being in the room but not present -- Not having a consistent design language -- Throwing deliverables over the fence -- Living in the deliverables -- Assuming others don't get design -- Insisting on perfection -- Responding to tone, not content -- Defending too hard -- Not defending hard enough -- Identifying and fixing your own anti-patterns -- Relaxation techniques at work -- Group design techniques
Includes bibliographical references and index
1
Keywords: Human-computer interaction -- Social aspects; User-centered system design -- Research